Effects of chronic treatment with gold nanoparticles on inflammatory responses and oxidative stress in Mdx mice. (2nd January 2020) - Haupenthal, Daniela Pacheco dos Santos; Possato, Jonathann Corrêa; Zaccaron, Rubya Pereira; Mendes, Carolini; Rodrigues, Matheus Scarpatto; Nesi, Renata Tiscoski; Pinho, Ricardo Aurino; Feuser, Paulo Emilio; Machado-de-Ávila, Ricardo Andrez; Comim, Clarissa M.; Silveira, Paulo Cesar Lock
Abstract: Duchenne muscular dystrophy (DMD) is an X-linked recessive hereditary myopathy characterised by progressive muscle degeneration in male children. As a consequence of DMD, increased inflammation and oxidative stress occur in muscle tissue along with morphological changes. Several studies have reported anti-inflammatory and antioxidant effects of gold nanoparticles (GNP) in muscle injury models. The objective of this study was to evaluate these effects along with the impacts of the disease on histopathological changes following chronic administration of GNP to Mdx mice. Two-month-old Mdx mice were separated into five groups of eight individuals each, as follows: wild-type (WT), Mdx-modified without treatment, Mdx + 2.5 mg/kg GNP, Mdx + 7.0 mg/kg GNP and Mdx + 21 mg/kg GNP. GNP with a mean diameter of 20 nm were injected subcutaneously at concentrations of 2.5, 7.0 and 21 mg/kg. Treatments continued for 30 d with injections administered at 48-h intervals. Twenty-four hours after the last injection, the animals were killed and the central region of the gastrocnemius muscle was surgically removed. Chronic administration of GNP reduced inflammation in the gastrocnemius muscle of Mdx mice and reduced morphological alterations due to inflammatory responses to muscular dystrophy. In addition, GNP also demonstrated antioxidant potential by reducing the production of reactive oxygen and nitrogen species, reducing oxidative damage and improving antioxidant activity.